2023
DOI: 10.1097/tp.0000000000004678
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance Spectroscopy in Heart Transplantation: Posttransplant Changes in Body Composition and Effects in Outcomes

Abstract: Background. Bioimpedance spectroscopy yields measurements of fat-free mass, fat mass, phase angle, and other measures. Bioimpedance spectroscopy has been validated as a preoperative assessment tool in cardiac surgical studies, in which low phase angle predicted morbidity and mortality. No studies have evaluated bioimpedance spectroscopy following heart transplantation. Methods. We evaluated body composition, nutrition status (Subjective Global Assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…72,73 And, in a study using BIS, the obtained phase angle at 50 Khz was shown to predict poor outcomes after heart transplant, in which patients with lower phase angle had higher risk of infection-related readmissions and prolonged posttransplant length of stay and increased mortality. 74…”
Section: Bioelectrical Impedancementioning
confidence: 99%
“…72,73 And, in a study using BIS, the obtained phase angle at 50 Khz was shown to predict poor outcomes after heart transplant, in which patients with lower phase angle had higher risk of infection-related readmissions and prolonged posttransplant length of stay and increased mortality. 74…”
Section: Bioelectrical Impedancementioning
confidence: 99%